DEVELOPMENT OF THE NATIONAL EDUCATION SYSTEM - Shabbazova Dilfuza Ruzikulovna,; Khaidarova Mahliyo Khabibullayevna,; Norgabilova Raykhona Davlatovna,; Azimova Dilfuza Usmonovna,; Khudaykulova Saida Zakirovna, (The Bioscan, 2025)
The aim of this research is to investigate the effectiveness of the current national education system in promoting equitable access to quality education; the key issue being addressed is the disparity in educational outcomes across different socioeconomic groups, necessitating a comprehensive analysis of quantitative data on student performance metrics and qualitative data from stakeholder interviews to identify barriers and potential improvements within the system. This dissertation investigates the effectiveness of the current national education system in promoting equitable access to quality education, with a particular focus on the disparities in educational outcomes across various socioeconomic groups. Through a comprehensive analysis of quantitative data on student performance metrics and qualitative insights gathered from stakeholder interviews, the research identifies significant barriers to educational equity, including resource allocation, curriculum relevance, and systemic biases. The findings reveal that students from lower socioeconomic backgrounds consistently underperform compared to their peers, highlighting a pressing need for targeted policy interventions and resource distribution strategies. The significance of these findings extends into health outcomes, as education is closely linked to health literacy, access to healthcare services, and overall wellbeing. Improved educational equity could lead to enhanced health outcomes, thereby reducing disparities in healthcare access and quality. Moreover, the broader implications of this study underscore the essential role that education plays in the social determinants of health, suggesting that reforming the national education system could have far-reaching impacts on public health initiatives, workforce development, and socioeconomic mobility. Ultimately, this research provides a critical foundation for future policy discussions and actions aimed at fostering a more equitable education system that supports all students, while simultaneously addressing the interconnected challenges posed by health disparities.